The Future of Sustainable Trade - Due Diligence Initiatives, Voluntary Sustainability Standards and Developing Countries - UN Trade; Development (United Nations, 2025)
International trade has been linked to various sustainability issues, such as deforestation, climate change, economic inequalities and violations of human rights. In response, private, voluntary trade governance instruments such as Voluntary Sustainability Standards (VSS) have emerged to promote sustainable practices within global value chains (GVCs) and have gained considerable grounds, especially in land use sectors. This document aims to: Map the new regulatory landscape of sustainability due diligence and its relationship with VSS. - Learn lessons from VSS on embedding sustainability concerns in management procedures and processes to inform the implementation of due diligence measures. - Identify and assess the potential impact of sustainability due diligence measures on producers in developing countries. - Draw recommendations to make sustainable trade governance initiatives such as due diligence measures and VSS more inclusive.